IDENTIFIKASI FAKTOR-FAKTOR RISIKO HIPERTENSI PADA MASYARAKAT DI RPTRA KELURAHAN TANJUNG DUREN - Maharani, Ni Putu Radela; Tamarifa, Zhaqina Azizah; Wulandari, Ainurrahmi; Diyan, Ikrimah; Djamal, Syifa Kamila; Maizura, Fanny Izzati; Wongso, Agnes Zenyka; Fadhil, Rafly Afif; Khusfiani, Triasti; Salma, Nabila Maudy; Adriani, Donna; Imran, Yudhisman (Jurnal Pengabdian Masyarakat Trimedika, 2024)
Background: Hypertension is defined as a condition where blood pressure persistently increases. PLANTATION (Prevention of Hypertension) 2024 is a social service activity carried out at the Rambutan RPTRA, Tanjung Duren which aims to identify risk factors that can cause hypertension. Method: 34 people participated in PLANTATION, which began with an anammesis , physical examination consisting of measurement of body mass index  (BMI), blood pressure, and current blood sugar. Then it ends with providing education about hypertension. Results: There were 17 out of 27 participants that had hypertension,  18 out of 27 participants were overweight , and from the current blood sugar results, the majority of participants who had diabetes were women and in the age group 46 -60 years. Conclusion: Risk factors of hypertension in the community in the RPTRA of Tanjung Duren District were identified as obesity and type 2 diabetes mellitus.